Inhaltliche und funktionale Eigenschaften von Datenbanken für systematische Literaturrecherchen - Nordhausen, Thomas; Hirt, Julian (GMS Medizin – Bibliothek – Information)
The justified selection of databases is a fundamental step in systematic literature searches. RefHunter supports this selection by providing standardized and comparable sheets of the content, functions and usage modalities of currently 106 databases (as of December 2024) related to healthcare. This inventory was systematically analyzed with regard to the characteristics of the databases. This analysis revealed considerable differences and more functions in licensed databases compared to freely accessible databases.